2009
DOI: 10.3727/096368909x474258
|View full text |Cite
|
Sign up to set email alerts
|

E-Cadherin Protects Primary Hepatocyte Spheroids from Cell Death by a Caspase-Independent Mechanism

Abstract: Cultivation of primary hepatocytes as spheroids creates an efficient three-dimensional model system for hepatic studies in vitro and as a cell source for a spheroid reservoir bioartificial liver. The mechanism of spheroid formation is poorly understood, as is an explanation for why normal, anchorage-dependent hepatocytes remain viable and do not undergo detachment-induced apoptosis, known as anoikis, when placed in suspension spheroid culture. The purpose of this study was to investigate the role of E-cadherin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 18 publications
(18 reference statements)
4
50
0
Order By: Relevance
“…Hepatocytes in aggregate or spheroid culture have been shown to be able to maintain viability and metabolic functions for a longer period than those in monolayer cultures, possibly due to the better retainment of in vivo hepatic morphological characteristics (33)(34)(35)(36). To further study the hiPSC-HPC aggregates, immunofluorescent stainings were performed on E-cadherin, an epithelial marker that had been shown to protect primary hepatocyte from apoptosis (37), and intracellular albumin, a functional hepatic marker. Aggregates after 7 d of culture were stained positively for both E-cadherin and albumin, demonstrating functional spheroid formation (Fig.…”
Section: In Vitro Structural Characterization Of 3d Hepatic Triculturmentioning
confidence: 99%
“…Hepatocytes in aggregate or spheroid culture have been shown to be able to maintain viability and metabolic functions for a longer period than those in monolayer cultures, possibly due to the better retainment of in vivo hepatic morphological characteristics (33)(34)(35)(36). To further study the hiPSC-HPC aggregates, immunofluorescent stainings were performed on E-cadherin, an epithelial marker that had been shown to protect primary hepatocyte from apoptosis (37), and intracellular albumin, a functional hepatic marker. Aggregates after 7 d of culture were stained positively for both E-cadherin and albumin, demonstrating functional spheroid formation (Fig.…”
Section: In Vitro Structural Characterization Of 3d Hepatic Triculturmentioning
confidence: 99%
“…There are different ways to induce the formation of spheroids including continuously-stirred bioreactors [94], the rocked suspension technique [95] and rotating wall bioreactors [96]. Initial experimentation demonstrated that, between spheroids and monolayers, there was indeed differential toxicity induced by 7 day methotrexate exposure.…”
Section: D Culturing Techniquesmentioning
confidence: 99%
“…The liver parenchyma is permeated by a collagenous fibrillar network, which is embedded in an extracellular matrix, mainly composed of a mixture of elastin, heparin sulfate proteoglycan and surface adhesion molecules, such as laminin and fibronectin [14]. The extracellular matrix, adhesion glycoproteins, Ca 2+ ions and cell surface receptors play an important role in maintaining cell anchorage, shape, polarity and function [15]. Variations of extracellular matrix content between different species result in the degree of difficulty.…”
Section: Hepatocyte Isolationmentioning
confidence: 99%
“…These kinds of essential factors were determined and supplement in the medium for keeping liver cells vigorous. Moreover, co-culture with other cell types may be responsible for re-establishing cell junctions such as E-cadherin which is required for hepatocyte spheroid formation [28], and protecting hepatocytes from cell death, thus is emerging as a prospective way to cultivate and maintain hepatocytes. Seeding the primary hepatocytes with mesenchymal stem cells [29], liver sinusoidal endothelial cells or umbilical vein endothelial cells [30] has been reported to result in enhanced heterotypic cell-cell interactions to form spheroids in a shorter time, which led to improvements in hepatocyte function and prolongation of the survival time.…”
Section: Hepatocyte Culturementioning
confidence: 99%